The environmental policy on maximum allowable limits (MPL) for mining effluents - Cerna Landa, Edith Carmen (2021)
In the contentious administrative processes followed with the Environmental Assessment and Enforcement Agency - OEFA, it has been noted that mining companies are permanently sanctioned by OEFA for exceeding the maximum permissible limits (MPL) in the mining effluents that they discharge into the environment. In this sense and based on the Principle of Prevention, it is necessary to adopt within the environmental policy of damage prevention, that OEFA control for such excess is carried out within the mining effluent treatment facilities, that is, before its discharge to the environment and not only in the control and monitoring points indicated in the environmental impact study, whose evaluation exclusivily it should be en charge of the National Service of Environmental Certification for Sustainable Investments - SENACE of the Ministry of the Environment - MINAM.